ANALISIS PENGARUH FAKTOR EVALUATIF WISATAWAN TERHADAP MINAT BERPERILAKU DI MASA DEPAN, DENGAN KEPUASAN SEBAGAI VARIABEL INTERVENING (Studi Pada Tempat Wisata Alam Umbul Sidomukti Semarang) - Fernaldi, Elmer Hafiizh; Sukresna, I Made (Diponegoro Journal of Management, 2017)
This study aimed to analyze the effects arising from the service quality and tourist experience on satisfaction and its influence on revisit intention and recommend intention from Umbul Sidomukti. The variables used in this study is service quality and tourist experience as an independent variable, then the satisfaction as an intervening variable lastly, the revisit intentionÂ  and recommend intention as the dependent variable. The sample in this study were 186 respondents that came from the tourist of Umbul Sidomukti Semarang.The method used is purposive sampling by distributing questionnaires to the respondents (tourist). In this study developed a theoretical model to propose eight hypotheses to be tested using analysis tools Structural Equation Modeling (SEM) which is operated through a program AMOS 22.0. Based on the research of data processing SEM for full model has met the criteria of goodness of fit as follows, the value of chi-square = 204,469; probability = 0,012; RMSEA = 0,038; CMIN/DF = 1,270; GFI = 0,903; TLI = 0,985; CFI = 0,988; NFI = 0,945, and a marginal criteria which is AGFI = 0,873. With the result, it can be said that this model is feasible to be used. The results showed that the revisit intention and recommend intention can be improved by increasing service quality that affect the satisfactionÂ  as a determinant of success to increase revisit intention and also recommend intention.